Just selection and preparation? CLIL effects on second language learning. (August 2022) - Feddermann, Maja; Baumert, Jürgen; Möller, Jens
Abstract: Since most studies failed to account for selection and preparation effects, previous studies overestimated the positive effects of Content and Language Integrated Learning (CLIL) on the development of students' receptive foreign language skills. We examined the English listening and reading comprehension development of N = 448 German CLIL and N = 4, 191 non-CLIL grammar school students from grade five to grade nine using full survey data from a 2014–2019 cohort. At the beginning of the study, students were on average M = 10.38 ( SD = 0.54) years old. Prior achievement and sociodemographic variables showed significant selection effects. After propensity score matching, data indicated significant preparation effects of additional English lessons. However, when both selection and preparation effects were controlled, no significant additive CLIL effect showed up. We discuss the results in light of earlier contradictory findings and recommend considering selection and preparation effects when studying CLIL effects. Highlights: Estimation of selection, preparation, and CLIL-effects on English competencies. Use of longitudinal full survey data and a large sample size. Conduction of propensity score matching. Significant selection and preparation effects. Non-significant additive CLIL effect.